Food Safety is an Important Public Health Issue: Chloramphenicol Residues Determination by Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) in honey - Krivohlavek, Adela; Žuntar, Irena; Ivešić, Martina; Andačić, Ivana Mandić; Šikić, Sandra (Psychiatria Danubina, 2014)
Honey is used for nutritional, medicinal and industrial purposes and antibiotic residues may harm its quality and constitute a danger to human health. The broad spectrum antibiotic chloramphenicol (CAP) was used for curative purposes in veterinary medicine, but is now forbidden in European Union (EU) because of its many serious side effects (e.g. aplastic anaemia, grey syndrome, severe bone marrow depression and hypersensitivity). The aim of this study was to facilitate analyses of the quality and safety of Croatian honey distributed to whole European Union market; an assessment that has not previously been made. CAP in honey was qualifying and quantifying by validated liquid chromatography tandem mass spectrometry with negative electrospray ionisation method (LC-MS/MS). The target antibiotic was separated on chromatographic column Zorbax SB C18 (150 mm x 2.1 mm, 3.5 μm) with a gradient elution using acetonitrile - 0.1% formic acid mobile phase at a flow rate of 0.3 mL/min, with column temperature 35°C for CAP and 5D-CAP as internal standard. Homogenised honey samples were diluted with acetate buffer solution and extracted on Oasis Hydrophilic-Lipophilic-Balanced (HLB) sorbents. The method was used to analyse 280 domestic honey samples collected throughout Croatia between 2005.-2013. Recoveries of the method for real (acacia, chestnut, linden and flower) honey samples were 102% with RSD 8.4%. The value CCα and CCβ were 0.09 and 0.12 μg/kg, respectively. Results showed only three subsequent positive detections (1.1%) of CAP in honey. Analysed honey samples from Croatia showed good quality and safety what is the one of the main objective in consumer health policy in EU.